Fenway and the frisbee trick - Coe, Victoria J.; Lew-Vriethoff, Joanne (G. P. Putnam's Sons, 2022)
"Fenway finds out catching a Frisbee in mid-air is much harder than it looks"--
Ages 5-8.
Keywords: Jack Russell terrier -- Fiction; Dogs -- Fiction; Human-animal relationships -- Fiction